The Use of Social Media Platforms as a Collaborative Supporting Tool: A Preliminary Assessment - Zabidi, Norsharina; Wang, Weigang (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Presently, social media platforms hold an excellent reputation as the closest subject and most comfortable interaction zone inside the learner’s heart which makes it the most influential learning tool. However, the evaluation of the social media platforms usage based on student’s choices primarily as their collaborative learning supporting tool is still in the small-scale study. Meanwhile, majority of the studies reported so far, focusing more on the usage of a particular type popular or famous social media platforms (e.g., Facebook, YouTube, Twitter and so on) as the collaborative supporting tool. This paper attempt to assess the use of overall social media platforms based on student choices, notably for supporting their collaborative learning activities. A questionnaire survey used for data collection from two universities in two countries. Findings showed that both of the universities’ students have actively utilised their social media platforms as their collaborative supporting tool with ’four times and more’ usage over a week, where it is already part of their daily lives. Another result also revealed the students spent their time using social media platforms at least for an hour’ in a week as their collaborative supporting tool. Conclusively, it implies that social media platforms are still relevant enough and play an indispensable part in supporting the learning process mainly, for collaborative activity context.